Evaluation of cookies produced from blends of wheat, cassava and cowpea flours - Abiodun Adekunle Olapade (International Journal of Food Studies, 2014)
Cassava (Manihot esculenta Crantz) and cowpea (Vigna unguiculata L. Walp) were processed into flours and used to substitute wheat flour for preparation of cookies. The chemical, including proximate composition and anti-nutritional factors, and functional and pasting properties of the blends were determined. Cookies were produced from the blends with 100% wheat flour as a control. The anti-nutritional factors, physical properties and organoleptic attributes of the cookies were evaluated. An increase in the level of cassava flour substitution resulted in a decrease in the protein content of the composite flour. However, addition of cowpea flour resulted in an increase in the protein content. There were significant (p<0.05) reductions in the studied anti-nutritional factors after baking. Cookies from composite flours were not significantly (p>0.05) different from the control in overall acceptability. This indicates the feasibility of producing nutritious cookies with desirable organoleptic qualities from cassava, wheat and cowpea composite flour.